Análise de investimentos financeiros : opção mais vantajosa para o mercado financeiro atual no segmento pessoa física - Lodi, Giânderson (2022)
Faced with the vast number of options that exist in terms of the financial investment segment, knowing the environment in which they are inserted, as well as the particularities that exist in each of the investments, is a mandatory task for anyone looking to invest in order to obtain gains within the financial market. In this sense, the present work aims to verify which are the investment options in private securities available in the financial market for the individual segment, which have the best return based on the history of the last 10 years. Methodologically, to meet the proposed objective, data on monthly rates from October 2012 to October 2022 were collected from the following investments: variation of the Ibovespa index, variation of the savings account index, variation of the CDI index that was used to calculate the profitability of CDB and LCI, and finally, the variation of the IPCA index. The processing of these data was done using Microsoft Exel, a platform used to calculate the profitability of the chosen assets, as well as to generate spreadsheets and graphs. It was concluded at the end of the research that direct Treasury bonds linked to the IPCA obtained the best results, with a net return of 182.16%. This type of investment obtained a result 26.44% higher than the result of the simulated CDB, which was the second with the best return. The least profitable investment in the simulation was the Savings Account.